The Role of Institutional, Societal, and Leadership Forces in Shaping Organizational Transparency A Qualitative Literature Review - Sugiharti, Tanti; Nurjaman, Roni (LPPM STIE Kasih Bangsa, 2025)
This qualitative literature review explores the role of institutional, societal, and leadership forces in shaping organizational transparency. By analyzing existing literature, the study identifies how these forces interact to form five archetypal transparency regimes: vanguard, pioneering, hollow, deceptive, and paradoxical. Institutional forces, through regulations and governance norms, provide a framework for transparency. Societal forces, driven by stakeholder pressure, motivate organizations to meet public expectations. Leadership forces contribute by fostering a culture of openness. The study highlights the complex interplay of these forces and offers insights into strategies for enhancing transparency. Despite its contributions, the study acknowledges limitations related to interpretative bias and the generalizability of findings across different contexts. Future research is recommended to empirically test these insights and explore diverse industrial and geographical settings.